The choice between deceased‐ vs living‐donor renal transplantation in children: Analysis of data from a Belgian tertiary center. (4th February 2018) - Van Cauwenberghe, Katty; Raes, Ann; Pauwels, Lut; Dehoorne, Jo; Colenbie, Luc; Dequidt, Clement; Dossche, Lien; Vande Walle, Johan; Prytuła, Agnieszka
Abstract: Pediatric renal transplantation with a living donor (LD) has superior outcome, but there is a paucity of studies analyzing the reasons for not undertaking living donation in West‐European countries. The aim of this study was to retrospectively review the choice of donor source in our center. We also aimed to identify factors which prevented transplantation with a LD. This retrospective study was performed including children aged 2‐19 years who underwent kidney transplantation (KT) at the Ghent University Hospital between 1996 and 2016. Relevant data were collected from medical files to identify the main medical, psychological, and socio‐economic factors influencing the choice of the donor source. There were 48 patients (boys n = 33) who underwent KT. Thirty‐nine patients received a deceased donor (DD) kidney and nine patients received a LD kidney. Sixteen of 48 transplantations were preemptive. The reasons for DD KT included socio‐economic factors such as single caregiver families, one or both parents with a criminal record or convictions and religious or cultural constraints (n = 15), medical considerations (n = 13), refusal of the close relatives/parents to donate (n = 7), and acceptance of an organ from a DD while prospective donor was undergoing medical screening (n = 4). The low incidence of living kidney donation can be explained by socio‐economic and medical factors. Refusal to donate is a potentially modifiable factor and strategies aimed at education and guidance of the families might contribute to a higher incidence of living donation in our setting.